2014
DOI: 10.1016/j.jand.2014.08.026
|View full text |Cite|
|
Sign up to set email alerts
|

Consensus Statement of the Academy of Nutrition and Dietetics/American Society for Parenteral and Enteral Nutrition: Indicators Recommended for the Identification and Documentation of Pediatric Malnutrition (Undernutrition)

Abstract: The Academy of Nutrition and Dietetics and American Society for Parenteral and Enteral Nutrition, utilizing an evidence-informed, consensus-derived process, recommend that a standardized set of diagnostic indicators be used to identify and document pediatric malnutrition (undernutrition) in routine clinical practice. The recommended indicators include z scores for weight for height/length, body mass index for age, length/height for age, or mid-upper arm circumference when a single data point is available. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
430
0
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 309 publications
(482 citation statements)
references
References 49 publications
5
430
0
19
Order By: Relevance
“…However, weight alone may be misleading as a marker of nutrition, especially in the PICU population where fluid shifts are commonly present during the acute phase of illness. Weight for height or BMI may provide a better index of nutritional status and were recently recommended as primary indicators of nutritional status and growth in children [31]. Lean body mass may be a better predictor of outcomes compared to weight alone [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, weight alone may be misleading as a marker of nutrition, especially in the PICU population where fluid shifts are commonly present during the acute phase of illness. Weight for height or BMI may provide a better index of nutritional status and were recently recommended as primary indicators of nutritional status and growth in children [31]. Lean body mass may be a better predictor of outcomes compared to weight alone [32].…”
Section: Discussionmentioning
confidence: 99%
“…We compared obtained data with current recommended norms of consumption for food ingredients, energy and food products for different population groups of Kyrgyz Republic (19). The malnutrition levels for children and adolescents were defined according to the generally accepted standards (13). The data were analyzed using software package Analysis ToolPack -VBA, EXCEL -6.0…”
Section: Methodsmentioning
confidence: 99%
“…The Chronic Kidney Disease in Children (CKiD) study (15), a large collaborative of children from North America with CKD who are not yet on dialysis, further defined these criteria in the context of pediatrics, including reference points which are pediatric specific, and also included poor growth in the diagnostic criteria, notably a height less than the third percentile or a decrease in growth velocity of more than 10%. This criteria is supported by general pediatric literature (16), including a joint position paper from the Academy of Nutrition and Dietetics (AND) and the American Society of Enteral and Parenteral Nutrition (ASPEN), noting that severe height stunting indicates repeat infections and/or chronic inadequate nutrition (17). The CKiD study revealed 7–20% of pediatric CKD patients have PEW (15).…”
Section: Impact Of Nutrition On Growth In Ckdmentioning
confidence: 99%